KARAKTERISASI BIOKIMIAWI RIZOBAKTERI ASAL GULMA BERDAUN LEBAR YANG BERPOTENSI SEBAGAI DELETERIOUS RHIZOBACTERIA - Asniah, Asniah; Rakian, Tresjia C.; Wangadi, Sri; Gusnawaty, HS (Jurnal Agroteknos, 2013)
The research aimed to know biochemical characters of rhizobacteria from broadleaf weed that are potential as deleterious rhizobacteria. The research was conducted at Agronomy Laboratory   of Agriculture Faculty   Halu Oleo University Kendari from January until March 2013. The results showed that   9 of 10 rhizobacteria isolates tested from broadleaf   weeds   rhizosphere   had   the   ability   to   solubilize   phosphate   with   different diameters. For nitrogen fixation ability, all isolates tested were potential but only isolates of ML-01 and KL-06 had high capability. All isolates had different ability to produce IAA, with isolates of   KL-06 produced higher concentration of   IAA (33,07 ppm) compared to other isolates. Isolates that had the ability to produce HCN  were isolates BL-07, with filter paper change from yellow to dark brown, and BL-08 and BL-03 light brown color changes indicated to that the production of  HCN  was increased. Result of research showed that some isolates tested had biochemical character as deleterious rhizobacteria by  the ability to solubilize phosphate, fix nitrogen, produce IAA and HCN. Keywords: biochemical characterization, rhizobacteria, broadleaf weeds, deleterious.